Literature Review on New Generation Cooperative Enterprise Architecture - Estiyan Dwipriyoko (Fakultas Teknik Universitas Langlangbuana, 2017)
Cooperative is a legally incorporated business organization, that built collectively by their member, and aim to fulfill their needs. New version of Cooperative is called New Generation Cooperative (NGC) that has characters as: NGC may issue shares, individuals may hold higher levels of equity through purchase of share, and membership may be limited to shareholders. Enterprise Architecture is the comprehensive conceptual design or blueprint of company and organization, which describes it’s the structures, function, and operations. The purpose of the research is to design the Enterprise Architecture for NGC. This NGC can be started as a low cost enterprise by implementing Open Business Model. The Open Business approach places value on transparency, stakeholder inclusion, and accountability. This research shall purpose the Technology part of Strategic Management, which can relate New Generation Cooperative Enterprise Architecture as new category for Open Business Model.